Psychology of Resistance in Psychoanalytic and Cognitive-Behavioural Theraphy Aproaches - Demers, Angelina Eduardovna (Psychological Prospects Journal, 2012)
Theoretical analysis of the resistance theory in psychoanalytical and cognitive-behavioural directions has been presented in the article. The approaches of work in accordance with parameters have been defined within two therapeutic approaches.